PENGARUH MODEL PEMBELAJARAN INKUIRI TIPE PICTORIAL RIDDLE TEHADAP PEMAHAMAN KONSEP FISIKA SISWA KELAS VIII SMP NEGERI 7 PALEMBANG - Wulansari, Sri; Lubis, Patricia; Andriani, Nely (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Research has been conducted to determine the effect of the inquiry learning model on the pictorial riddle type on the understanding of the physics concepts of eighth grade students of Palembang State Junior High School 7. Riddlel pictorial type inquiry is a learning model to develop student motivation and participation from small / large group discussions in the form of images that are used as a source of discussion so that they can find answers to a problem in question. The method used in this study is the method of Quasi Experiment, with the design of the matching only post-test control group design and cluster random sampling retrieval technique divided into two classes, namely class VIII.11 as the experimental class which received learning treatment using the pictorial type inquiry learning model riddle, and class VIII.9 students as control classes who were treated using inquiry learning models. The collection technique uses tests. The analysis technique used in this study is the t-test of the right side. The results of the calculation of data analysis obtained the average value of the experimental class 81 and the mean of the control class 75.16, with a significant level of α = 0.05 obtained ttable ie 1.67 based on the calculation results there is a significant influence of the pictorial riddle type learning model towards understanding the physics concept of eighth grade students of Palembang State Junior High School 7.